ESTIMASI DOSIS RADIASI YANG DITERIMA PASIEN PADA PEMERIKSAAN THORAX PA - Kadek Sari Anggarin; I Putu Irma Wulandari; Ni Putu Rita Jenyanthi (JRI (Jurnal Radiografer Indonesia), 2022)
Background : Radiation dose received by patients during medical radiology examination varied among practices. This is due to difference in techniques, filter, and equipment used during examinations. This study aims to determine the value of facilities Diagnostic Reference Level (fDRL) in Radiology hospitals district Buleleng and comparison of the 75th percentile value of radiation dose received by adult Thorax PA patients with the standards established by BAPETEN. Methods: This type of research uses a quantitative method with a survey conducted at the Radiology Installation of Buleleng Regency Hospital in February 2020. The population of this study was all patients who underwent radiographic examination of Thorax PA adults (over 15 years). While the sample in this study was 30 patients with Thorax PA radiography examination adult (over 15 years). Absorbent dose measurement data is carried out directly with a digital dosimeter measuring device and then processed using SPSS. Results and Conclusion: The results of this study obtained the value of facilities Diagnostic Reference Level for examination of adult PA Thorax in Radiology Installation of Buleleng Regency Hospital is 0.0275 mGy and the percentile value of 75 absorbent doses received by PA thorax patients adult in Radiology Installation of Buleleng Regency Regional Hospital is 0.0275 mGy where the dose Radiation absorption received by PA thorax patients has met the standards set by BAPETEN in the Indonesian Diagnostic Reference Level (IDRL) 2019 radiation absorbed dose received by adult thorax PA patients, which is 0.4 mGy.